E-072 50 Shades of Gradients: Does the Pressure Gradient in Venous Sinus Stenting for Idiopathic Intracranial Hypertension Matter?. (29th July 2016) - McDougall, C; Beecher, J; Shen Ban, V; Fiesta, M; Barr, J; White, J; Novakovic, R; Pride, G; Welch, B
Abstract : Introduction: Idiopathic intracranial hypertension (IIH) is a relatively uncommon, poorly understood disease that is often difficult to treat. First line medical and surgical therapies are often ineffective. Venous sinus stenosis is found in the vast majority of patients with IIH and venous sinus stenting (VSS) has been demonstrated to be effective in a select patient group. Identifying which patients will benefit from stenting remains unclear. One strategy is to measure the pressure gradient across the stenosis using retrograde transvenous manometry. Many authors have adopted a strategy whereby VSS is offered to patients with a pressure gradient above a certain threshold. This number is variable between different operators. In this study we reviewed the literature to try and establish what if any evidence exists to support a relationship between the pressure gradient across the stenosis and clinical outcomes. Materials and methods: We systematically reviewed the English literature for studies reporting both the pressure gradients across the stenosis for each patient and the individual patient outcomes. Data was then analyzed for statistical correlations between the pressure gradient and the outcome. Results: We identified 85 patients from 13 studies in which both the pressure gradient and clinical outcomes were reported for each patient. ANOVA comparing gradients with outcomes was not significant ( p = 0.06). Student's t- test analysis of the groups with a dichotomization between the group with favorable outcomes and those with unfavorable outcomes was also not significant ( p = 0.13). The pressure gradient was not found to be a statistically significant predictor of outcome on univariate logistic regression analysis ( p = 0.15). Conclusion: Venous sinus stenting for IIH appears to have good clinical results in selected cases. However, from the available reported cases in the literature, there does not appear to be any correlation between an increasing pressure gradient across the region of stenosis and the chances of an improved outcome. These findings underscore the need for further study of IIH and reflect our incomplete understanding of its exact pathophysiology. Disclosures: C. McDougall: None. J. Beecher: None. V. Shen Ban: None. M. Fiesta: None. J. Barr: None. J. White: None. R. Novakovic: None. G. Pride: None. B. Welch: None.